2016
DOI: 10.19082/1693
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological comparisons of open vein harvesting and endoscopic vein harvesting in coronary artery bypass grafting patients in Mashhad

Abstract: IntroductionHarvesting of the greater saphenous vein is almost an inevitable part of coronary artery bypass grafting (CABG) operations, and it is done by two main techniques, i.e., conventional or open vein harvesting (OVH) and the minimally-invasive endoscopic vein harvesting (EVH). This study aimed to compare these two techniques in off-pump CABG procedures with respect to clinical and pathological outcomes.MethodsThis cohort study was conducted on CABG candidates during a one-year period from October 2013 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Moeinipour, et al also supported this finding. In a study showing that patients in the endoscopic-vein harvesting group have experienced less pain than patients in the open-vein harvesting group and pain scores during the 6-week follow-up were significantly reduced [8].…”
Section: Patient's Satisfaction With Appearance and Postoperative Painmentioning
confidence: 98%
See 2 more Smart Citations
“…Moeinipour, et al also supported this finding. In a study showing that patients in the endoscopic-vein harvesting group have experienced less pain than patients in the open-vein harvesting group and pain scores during the 6-week follow-up were significantly reduced [8].…”
Section: Patient's Satisfaction With Appearance and Postoperative Painmentioning
confidence: 98%
“…During the follow-up period, antibiotics were administered to 14.4% of the patients in the open-harvest group compared to only 4.6% of the patients in the endoscopic-harvest group. The prior investigation by Moeinipour, et al in 2016 studied 87 patients who underwent endoscopic-vein harvesting, have implemented that the reason of the zero-infection rate observed with the endoscopic-vein harvesting patients is due to the smaller incisions and preserved tissue perfusion with this approach [8]. A study by Nezafati, et al concluded that in order to decrease wound related complications associated with the extensive incisions, endoscopic vein harvesting is recommended to reduce wound complications, leg wound infection and hematoma.…”
Section: Wound Related Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the efficiency of EVH and OVH is similar. Nevertheless, further research is needed to probe into its cosmetic outcomes, cost-efficiency, and hospital costs; it is even more essential to study the long-term graft patency of the EVH technique [16].…”
Section: Type Of Graftsmentioning
confidence: 99%
“…A frequent choice in coronary artery bypass grafting (CABG) operations is to harvest the greater saphenous vein, which is primarily performed through two procedures as minimally-invasive endoscopic vein harvesting (EVH) and open vein harvesting (OVH) (1).…”
Section: Introductionmentioning
confidence: 99%